On the "Preconditioning" Function Used in Planewave DFT Calculations and Its Generalization (Communications in Computational Physics, 2018)
The Teter, Payne, and Allan "preconditioning" function plays a significantrole in planewave DFT calculations. This function is often called the TPA preconditioner.We present a detailed study of this "preconditioning" function. We develop ageneral formula that can readily generate a class of "preconditioning" functions. Thesefunctions have higher order approximation accuracy and fulfill the two essential "preconditioning"purposes as required in planewave DFT calculations. Our general classof functions are expected to have applications in other areas.